2018
DOI: 10.20944/preprints201809.0224.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Distinct Pattern of Circulating Amino Acids Characterizes Older Persons with Physical Frailty and Sarcopenia: Preliminary Results from the BIOSPHERE Study

Abstract: Physical frailty and sarcopenia (PF&S) are hallmarks of aging that share a common pathogenic background. Perturbations in protein/amino acid metabolism may play a role in the development of PF&S. In this preliminary study, 68 community-dwellers aged 70 years and older, 38 with PF&S and 30 non-sarcopenic, non-frail controls (nonPF&S), were enrolled. A panel of 37 serum amino acids and derivatives was assayed by UPLC-MS. Partial Least Squares Discriminant Analysis (PLS-DA) was use… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Regarding muscle functionality, the reduction in walking performance and in endurance associated with a perception of exhaustion are all characteristic of sarcopenia [98]. Two of the early symptoms/signs of sarcopenia are, in fact, feeling weak and difficulty rising from a chair, leading to reduced ADL performance [99]. Recently, Patino-Hernandez et al [100] reported an association between two of the sarcopenia-defining variables (abnormal gait speed and handgrip strength) with fatigue.…”
Section: Sarcopeniamentioning
confidence: 99%
“…Regarding muscle functionality, the reduction in walking performance and in endurance associated with a perception of exhaustion are all characteristic of sarcopenia [98]. Two of the early symptoms/signs of sarcopenia are, in fact, feeling weak and difficulty rising from a chair, leading to reduced ADL performance [99]. Recently, Patino-Hernandez et al [100] reported an association between two of the sarcopenia-defining variables (abnormal gait speed and handgrip strength) with fatigue.…”
Section: Sarcopeniamentioning
confidence: 99%
“…Sarcopenia, a complex illness, has been associated with multiple risk factors, such as decreased physical activity, reduced caloric intake, chronic in ammation, degradation of the neuromuscular junction, and oxidative stress [9,10] . Oxidative stress results from various variables, including disturbances in intercellular conduction, mitochondrial malfunction, in ammation, and the buildup of reactive oxygen species [11,12] . Therefore, the implementation of strategies aimed at mitigating the detrimental effects of oxidative stress-induced damage presents itself as a promising avenue for the prevention of sarcopenia.…”
Section: Introductionmentioning
confidence: 99%